Heat plasticization of starch by extrusion in the presence of plasticizers - Borycki, J.; Wilczek, M.; Kolendo, A. Yu. (Polimery, 2022)
Polyesterimides (PESI - Table 1 and 2) were obtained in the reaction of selected chlorides of diacids, containing imide groups, with glycols or in the reaction of diacids with glycols' acetates. Polyamidoimides (PAMI - Table 3 and 4) were prepared in the reaction of selected chlorides of diacids with diamines. The conditions of the particular types of syntheses were presented in detail. The selection of various substrates let to obtain a diverse range of polymers differing in chemical structure. In contrast to PESI, PAMI polymers show good solubility in polar solvents (DMF, DMSO) in low concentrations (up to 1 wt. %). Specific viscosity of PAMI solutions in DMF suggests low molecular weight. IR spectra (Fig. 1 and 2) confirm the presupposed chemical structure of PESI and PAMI obtained (Scheme A-D). It was found by derivatography that PAMI showed good thermal stability (Fig. 3). The measurements of specific optical rotation of PAMI show that they are optically active. On the basis of measurements of contact angle with four various measurement liquids (Table 5) the surface free energy (SEP) and SEP components of PAMI (Table 6) were calculated using the method of Owens-Wendt or van Oss's one.